Subject Preferences and Psychological Implications of Portable Oxygen Concentrator Versus Compressed Oxygen Cylinder in Chronic Lung Disease. - Moretta, Pasquale; Molino, Antonio; Martucci, Michele; Fuschillo, Salvatore; De Felice, Alberto; Guida, Pietro; Motta, Andrea; Vitacca, Michele; Maniscalco, Mauro (Respiratory Care, 2021)
BACKGROUND: Oxygen therapy represents the elective therapy to improve the quality of life for patients with chronic respiratory diseases like COPD and interstitial lung disease. Lightweight portable oxygen concentrators (POCs) are a valid alternative to traditional systems such as portable compressed oxygen cylinders. However, patient preference and the possible psychological implications related to the use of both devices have been poorly assessed. We sought to evaluate patient preference between the ambulatory oxygen systems (ie, a POC or a small cylinder) for patients with COPD and interstitial lung disease experiencing exertional desaturation in a rehabilitation setting. Furthermore, the use of one device in comparison with the other was related to specific mechanical characteristics and related to perceived quality of life, anxiety, and depressive symptoms. METHODS: 30 subjects with COPD and interstitial lung disease, who demonstrated exertional desaturation on room air during 6-min walk test (6MWT), were recruited. Each subject performed 2 6MWTs, in random order: one breathing oxygen via a POC and one with a portable compressed oxygen cylinder. Both devices were set up to ensure oxyhemoglobin saturation between 92% and 95% during the 6MWTs. All subjects completed a questionnaire assessing anxiety, depression, and quality of life. Each device was randomly assigned to each subject for 1 week, and then replaced with the other in the following week. At the end of the trial period, all subjects completed a questionnaire evaluating several aspects of the oxygen therapy devices. RESULTS: There were no significant differences in oxygen saturation or the mean distances achieved during the 6MWTs between the 2 portable oxygen devices. The subjects expressed greater preference for the POC (73.3%), basing their choice mainly on ease of transport and lower weight. Subjects' age also correlated with preferences: younger subjects were more negatively focused on the weight of the portable compressed oxygen cylinder, whereas older subjects considered the POC easier to manage. No significant differences in preferences were present between COPD and interstitial lung disease. CONCLUSIONS: The POC and the portable compressed oxygen cylinder performed in a comparable manner during 6MWT for subjects with COPD and interstitial lung disease and exertional desaturation. Subjects preferred the POC because it was associated with better mobility.